Modelling and optimisation for sustainable development policy assessment - Cannon, M; Kouvaritakis, B; Huang, G (2005)
Earlier work on sustainable development devised a policy assessment tool that was based on a static optimisation formulation. Key ingredients in sustainable development problems are the presence of random effects and the conflict between different objectives. To accommodate these, the earlier formulation was strongly stochastic and was posed in a multi-objective framework. The purpose of this paper is to consider the extension of the work to a formulation that deploys dynamic optimisation. In particular it is the aim here to use simulations based on a large scale model to derive dynamic rather than static representations, to integrate these into the optimisation scheme and to assess the benefits. © 2004 Elsevier B.V. All rights reserved.